Med javno zdravstveno službo in tržnim izvajanjem zdravstvene dejavnosti - Strban, Grega (Delavci in delodajalci, 2025)
Who should be responsible for providing income security when sickness or injury occur, is one of the fundamental questions. Both may present a private risk, for which responsibility lies with the private person, his or her employer and private insurances, or a social risk, for which security shall be provided by social security scheme, the state and local communities. Slovenian legislature tackled the reshaping of healthcare provision to enhance the access to medical services and medicinal goods, such as medical aids and medicines. From mandatory health insurance point of view, it has focused on the procedure of enforcing the rights first and not their substance. That shall be done with the amendments to the health care and health insurance act at a later stage. Legislative endeavours have to stem from the health needs of inhabitants and not only the health delivery system and healthcare providers as such.
Keywords: health services; healthcare; healthcare provision; izvajalec zdravstvene dejavnosti; izvajalec zdravstvenih storitev; Javne službe; mandatory health insurance; mreža javne zdravstvene službe; obvezno zdravstveno zavarovanje; public healthcare network; zdravstvena dejavnost; Zdravstvo